[dis]Connected 00:06:05 | Towards a cyberpunk architecture - Hyun Jun Park (Architecture Image Studies Scientific Journal)
This article investigates the ways in which cyberspace inspired speculative architecture in recent decades. It focuses particularly on the characteristics and spatial potential of cyberspaces in Science Fiction literature, films and architecture. This article presents a short SF narrative developed from an award-winning short film, Hyper-Place, which the author created in 2009. Inspired by the notions of the Baudrillardian worldview, the film shares Masamune (1989), Mamoru (1995, 2001), and Wachowski’s (1999–2003) visions for cogno-technology in a cyberpunk context, especially uploaded consciousness, and it examines the spatial characteristics and potential for cyberspace. The architecture of this short cyberpunk narrative is 365 seconds and infinitely looped. The text takes an experimental position to represent multiple consciousnesses, and dual languages (English/Korean)  to voice the multi-consciousnesses of the Green Brick Room. The Korean text takes the form of ‘Coding Script’ to represent a ‘background system log’. As the narrative has a cyclical structure, it starts again after one of its loops. Thus, like cyberspace, the text’s potential signification(s) remain open-ended.